2020
DOI: 10.1177/1942778620910900
|View full text |Cite
|
Sign up to set email alerts
|

Fried eggs and all-women gangs: the geopolitics of Chinese gold mining in Ghana, bodily vulnerability, and resistance

Abstract: Between 2008 and 2016, more than 50,000 Chinese citizens migrated to Ghana to mine gold on small-scale concessions. This is particularly surprising given that small-scale mining is an activity reserved for Ghanaian citizens. Foreign gold mining is mediated by various intersecting political economic and geopolitical shifts, including unprecedented gold demand, economic crisis, and informal conditions to Chinese loans. Based on long-term, mixed-methods fieldwork, and drawing from feminist geopolitics research, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Moreover, the test of association of the respondents’ employment status with respect to participation in galamsey operations was not statistically significant (p-value = 0.054 > 0.05). This finding goes to buttress the findings from the steadily growing literature that reported that galamsey has become the most attractive informal sector job in developing countries ( Hausermann et al., 2020 ; Osumanu, 2020 ; Tuokuu et al., 2020 ; Mabe et al., 2021 ).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Moreover, the test of association of the respondents’ employment status with respect to participation in galamsey operations was not statistically significant (p-value = 0.054 > 0.05). This finding goes to buttress the findings from the steadily growing literature that reported that galamsey has become the most attractive informal sector job in developing countries ( Hausermann et al., 2020 ; Osumanu, 2020 ; Tuokuu et al., 2020 ; Mabe et al., 2021 ).…”
Section: Resultsmentioning
confidence: 53%
“…And if not for the growing illegality and massive environmental destructions associated with the operations, ASM is the exclusive right of the natives ( Akabzaa and Darimani, 2001 ; Ofosu-Mensah, 2010 ). Additionally, the position of migrants in the galamsey sector has been highlighted ( Nyame et al., 2009 ; Hilson et al., 2014 ; Antwi-Boateng and Akudugu, 2020 ), but fortunately for the Upper West Region, the devastating environmental effect of the illegal Chinese migrants including worsening social consequences in local mining communities as reported by a large body of the literature ( Hilson et al., 2014 ; Hilson, 2017 ; Botchwey and Crawford, 2018 ; Antwi-Boateng and Akudugu, 2020 ; Hausermann et al., 2020 ) were dim in this study.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…While a feminist geopolitics approach examines how such doings and sayings impact bodily vulnerability and experiences [53,54], researchers also examine and practice ways to build more just and livable worlds [55,56]. Much of this work explores resistance as small, gendered, and everyday acts.…”
Section: Feminist Geopoliticsmentioning
confidence: 99%